Thinking and doing: the effects of dopamine and oxytocin genes and executive function on mothering behaviours. (21st October 2016) - Tombeau Cost, K.; Unternaehrer, E.; Plamondon, A.; Steiner, M.; Meaney, M.; Atkinson, L.; Kennedy, J. L.; Fleming, A. S.; ,
Abstract : Animal and human studies suggest that initial expression of maternal behaviour depends on oxytocin and dopamine systems. However, the mechanism by which these systems affect parenting behaviours and the timing of these effects are not well understood. This article explores the role of mothers' executive function in mediating the relation between oxytocin and dopamine gene variants and maternal responsiveness at 48 months post‐partum. Participants ( n = 157) were mothers recruited in the Maternal Adversity, Vulnerability and Neurodevelopment Study, which assesses longitudinally two cohorts of mothers and children in Canada. We examined single nucleotide polymorphisms (SNPs) related to the dopamine and oxytocin systems ( DRD1 rs686, DRD1 rs265976, OXTR rs237885 and OXTR rs2254298), assessed mothers' decision‐making at 48 months using the Cambridge Neurological Automated Testing Battery (CANTAB) and evaluated maternal responsiveness from videotaped interactions during the Etch‐A‐Sketch co‐operation task. Mediation analyses showed that OXTR rs2254298 A‐carriers had an indirect effect on positive parenting which was mediated by mothers' performance on decision‐making task (estimate = 0.115, P < 0.005), while OXTR rs2254298 A‐carriers had both direct and indirect effects on physically controlling parenting, also mediated through enhanced performance on decision‐making (estimate = −0.059, P < 0.005). Dopamine SNPs were not associated with any measure of executive function or parenting (all P > 0.05). While oxytocin has previously been associated with only the early onset of maternal behaviour, we show that an OXTR polymorphism is involved in maternal behaviour at 48 months post‐partum through mothers' executive function. This research highlights the importance of the oxytocin system to maternal parenting beyond infancy. Abstract : Oxytocin receptor genotype predicts enhanced cognitive decision‐making, which mediates the relationship between oxytocin receptor genotype and both positive parenting and physically controlling parenting.